Greek and Byzantine philosophical exegesis - Despotis, Athanasios; Wallace, James Buchanan (Eastern church identities, 2022)
Intro -- Contents -- Chapter 1 Introduction: The Early Christian Philosophy as a Way of Life and an Art of Exegesis -- Chapter 2 Jesus als neuer Sokrates in Joh 1-12 -- Chapter 3 The Question of Origen's Conversion, His Concept of Conversion, and Its Relevance to His Biblical Exegesis -- Chapter 4 The Strategy and Functions of Philosophical Exegesis in Origen of Alexandria -- Chapter 5 Between the Mirror and the Face: Gregory of Nazianzus and Augustine on 1 Cor 13:12 -- Chapter 6 The Inextricability of Hermeneutics and Metaphysics in Late Neoplatonism and Patristic Theology -- Chapter 7 Providence, Ethics, and Exempla: Reassessing the Stoicism of John Chrysostom's Quod nemo laeditur nisi a se ipso -- Chapter 8 The Towers of Jerusalem and Ontological Presuppositions of Creation: Exegesis and Philosophy in Maximus the Confessor's Quaestiones ad Thalassium -- Afterword -- List of Contributors -- Index of Ancient Authors and Other Ancient Figures -- Index of Subjects.